2018
DOI: 10.1063/1.5010348
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced terahertz magnetic dipole response by subwavelength fiber

Abstract: Dielectric sub-wavelength particles have opened up a new platform for realization of magnetic light. Recently, we have demonstrated that a dipole emitter by a subwavelength fiber leads to an enhanced magnetic response. Here, we experimentally demonstrate an enhanced magnetic dipole source in the terahertz frequency range. By placing the fiber next to the hole in a metal screen, we find that the radiation power can be enhanced more than one order of magnitude. The enhancement is due to the excitation of the Mie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It is shown that a subwavelength aperture can be approximated with a MD source provided that the diameter is less than 0.3l [4]. Using numerical modelling (CST microwave studio), we confirm that a 300µm aperture excited with a x-polarized plane wave acts as a y-oriented MD in THz [4]. Moreover, we have shown that maximum transmission of the hybrid system occurs when the fiber diameter is similar to that of the aperture [4].…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…It is shown that a subwavelength aperture can be approximated with a MD source provided that the diameter is less than 0.3l [4]. Using numerical modelling (CST microwave studio), we confirm that a 300µm aperture excited with a x-polarized plane wave acts as a y-oriented MD in THz [4]. Moreover, we have shown that maximum transmission of the hybrid system occurs when the fiber diameter is similar to that of the aperture [4].…”
Section: Resultsmentioning
confidence: 54%
“…1(a). It is shown that a subwavelength aperture can be approximated with a MD source provided that the diameter is less than 0.3l [4]. Using numerical modelling (CST microwave studio), we confirm that a 300µm aperture excited with a x-polarized plane wave acts as a y-oriented MD in THz [4].…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…This has led to investigation of MD response in vicinity of nanostructures such as planar structures, nanospheres and metamaterials, using Green function approach 33 . Although enhancement of an MD source at the vicinity of subwavelength fiber has been observed experimentally 38 , there is no analytical model to investigate the interaction of MD in the vicinity of a nanofiber.…”
Section: Introductionmentioning
confidence: 99%